Cardiac and Metabolic Effects of Bariatric Surgery Among Obese Patients in a Malaysian Tertiary Hospital:: A 6-month Prospective Cohort Study - Roslan, Mohd Haidir; Raffali, Mohd Asyiq; Mohamad, Shawal Faizal; Kosai Nik Mahmood, Nik Ritza; Che Hassan, Hamat Hamdi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objective. Obesity is known to be associated with left ventricular diastolic dysfunction due to its effect on blood pressure and glucose tolerance. We aimed to investigate whether weight loss after bariatric surgery might improve diastolic dysfunction through in-depth echocardiographic examination. Methodology. We recruited twenty-eight patients who were about to undergo bariatric surgery by purposive sampling. They underwent echocardiography at baseline and 6 months after surgery with a focus on diastolic function measurements and global longitudinal strain (GLS). They also had fasting serum lipid and glucose measurements pre- and post-surgery. Results. The mean weight loss after surgery was 24.1 kg. Out of the 28 subjects, fifteen (54%) initially had diastolic dysfunction before surgery. Only two had persistent diastolic dysfunction 6 months after surgery. The mean indexed left atrial volume 6 months post-surgery was 27.1 from 32 ml/m2 prior to surgery. The average E/e’ is 11.78 post-surgery from 13.43 pre-surgery. The left ventricular GLS became (-)25.7% after surgery from (-)21.2% prior to surgery. Their post-surgery fasting serum lipid and glucose levels also showed significant improvement. Conclusion. Our study reinforced the existing evidence that bariatric surgery significantly improved echocardiographic parameters of diastolic function and left ventricular global longitudinal strain, along with various metabolic profiles.